1992
DOI: 10.1007/bf01321290
|View full text |Cite
|
Sign up to set email alerts
|

Child psychopathology and deviant family hierarchies

Abstract: The association between child psychopathology and reversals in family hierarchies ( Structural family theorists (Minuchin, 1974) have hypothesized that families seeking therapy for a dysfunctional child show evidence of hierarchical reversals (Haley, 1976) in the family structure, where the child has more or equal status or "power" than the parent(s). There have only been a handful of empirical studies which have examined this thesis, which has 1Senior Research Principal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Early reports found that parental psychopathology and substance abuse were more related to CD (Frick et al 1991) than ODD (Frick et al 1992). Deviant or inappropriate parenting practices have been more strongly associated with CD than ODD in some studies (Burke et al 2003;Lindahl 1998), but not others (Frick et al 1992;Green et al 1992). Using one of the largest clinically referred samples, Greene and colleagues (2002) found that ODD+CD (vs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Early reports found that parental psychopathology and substance abuse were more related to CD (Frick et al 1991) than ODD (Frick et al 1992). Deviant or inappropriate parenting practices have been more strongly associated with CD than ODD in some studies (Burke et al 2003;Lindahl 1998), but not others (Frick et al 1992;Green et al 1992). Using one of the largest clinically referred samples, Greene and colleagues (2002) found that ODD+CD (vs.…”
Section: Introductionmentioning
confidence: 92%
“…Relatedly, most of the early studies did not report whether children diagnosed with CD also met research criteria for comorbid ODD, nor did they include multiple measures from several contextual domains, which could have significantly limited their results. Further, early studies generally included only boys (e.g., Frick et al 1992;Frick et al 1991;Green et al 1992). Given increased attention to antisocial behavior in girls (Pajer 1998) and recent findings suggesting similar social and family risks for DBDs in both sexes (Messer et al 2006), whether younger girls experience problems in contextual domains comparable to those of younger boys is an important issue to examine.…”
Section: Introductionmentioning
confidence: 98%
“…While there is little evidence that problematic family structures are a direct cause of child problems, they can certainly maintain them. Green, Loeber, and Lahey (1992) showed that hierarchical structures tend to become disorganised when a family has a problem child. Typically, boundaries between parent, child, and extended family systems become unclear, the parents' relationship becomes conflicted, and the extended family may get caught in the battles during the many failed attempts to manage the problem child.…”
Section: Systems Theorymentioning
confidence: 99%
“…Further research is need to clarify this area; however, the review by Sines (1987) concluded that marital discord is found equally in other clinic and nonclinic children. Further, a recent study (Green, Loeber, & Lahey, 1992) found no evidence that depression in children is associated with deviant family hierarchies (Haley, 1976;Minuchin, 1974) in which the child exercises more power in the family than the parents.…”
Section: Studies Of Family Process Family Process and Childhood Deprementioning
confidence: 98%